Pretend play as the space for development of self-regulation: cultural-historical perspective - Bredikyte, Milda; Brandisauskiene, Agne (Frontiers in Psychology, 2023)
Self-regulated behavior is a prerequisite for learning and success in life. Considerable research confirms that mature forms of play support the development of self-regulation in the early years. This study explores the relationship between (3-6-year-olds) children's pretend play and self-regulation skills. Teachers filled out a Child's Play and Self-Regulation Checklist evaluating the level of children's play and self-regulation skills. The findings revealed that the levels of children's play and self-regulation skills are statistically significantly linked: the better the child performs an assumed role in play activity, the higher the level of their self-regulation. The results also suggest that a child's playing skills, gender, and age predict children's self-regulation skills manifested in play activity. 1 Introduction There has been a shift in educational thinking and practice in recent decades. Advances in research in several scientific fields brought the understanding that how well students do in school and later in life can be determined by how well they self-regulate (